Design of A Control Strategy for Gantry Crane Systems - Abdul Kadir Muhammad (Teknik Mesin "TEKNOLOGI", 2011)
The aims of this research are to identify a gantry crane process, analyze its model, design appropriate controllers and implement them on laboratory scale. As objectives, the controllers which have been designed should meet the specifications: stable, no steady state error, no overshoot and as fast as possible of settling time. The system consists of a gantry crane and its load, an electromotor as actuator and its transmission system, an angle and velocity sensor, a box which is A/D and D/A converter and a USB interface towards a laptop. Mathematical and experimental model analyzing have been used to analyze the system. Software tools namely Matlab Simulink is used for modeling, analyzing and design the controller, and the LabView application program is used for measurements, steering signals and implementation of the controller. Specifically, the root locus method has been used in designing the controller.Simple proportional controllers have been designed for the crane and its pendulum with gains of 3 and -4 respectively. After applied the proportional controllers and some tuning to find the optimal point of the controllers, a stable system with settling time of 98 % final value about 0.825 seconds, no overshoot and zero steady state error is achieved. So, all of the controllers requirements are fulfilled. Keywords: Crane, modeling, controller.